The Influence of Parental Involvement and Children's use of ICT Social Studies Learning Results - Erlina, Erlina; Amanah, Siti (Program Magister Teknologi Pendidikan Universitas Jambi, 2016)
This study aims to determine the effect of parent involvement and ICT utilization of student learning outcomes. Aspects analyzed include the influence of parental involvement in supporting student learning outcomes, utilization of ICT in supporting student learning outcomes. This research uses survey design with data collection instrument in the form of questionnaire. The population of the study were the students of class IX Junior high school 7 Kota Jambi. Sampling by random sampling based on the class with the amount of 125 people, This research was conducted by using double regression with hypothesis test at level of significance 0,05. The result of the research shows that: (1) there is a positive influence between parent involvement on student learning result, (2) there is positive influence between ICT utilization to student learning result, (3) there is a positive influence between parent involvement and ICT utilization together towards student learning outcomes. Based on the findings of the above research results it can be concluded that the involvement of parents and the utilization of ICT have an influence on student learning outcomes. To parents to spend more time accompanying their children in the learning process and in the utilization of ICT to support the child's learning process, and cooperation with teachers needs to be optimized to support the success of children.